Guided Imagery And Progressive Muscle Relaxation In Cancer Patients Undergoing Chemotherapy : A Literature Review - Agis Taufik; Nuriya (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
ABSTRACT Introduction: Cancer is one of the health problems with a rapid increase in incidence and proven to be the second leading cause of death in the world today. Cancer is also a common problem that occurs in the elderly who suffer from the predicted increase in 605 million in 2000 to 2 trillion in 2050 (Shahriari et al., 2017). Therapy that is often done by patients is by doing chemotherapy, but by doing chemotherapy there are many side effects on the patient's physical and psychological. Interventions that can be given in addition to pharmacological drugs are alternative or complementary therapies. Independent intervention that can be done by nurses in patients given Progressive Muscle Relaxation (PMR) therapy and guided images (GI). Method: Search is done electronically using a database, including google scholer and sch from May 2019 to June 2019. The keywords used are